Assessing outcomes in a lupus nephritis cohort over a 40-year period. (28th October 2020) - Gisca, Eugeniu; Duarte, Leila; Farinha, Filipa; Isenberg, David A
Abstract: Objectives: To characterize a LN cohort over 40 years, assessing its evolution, analysing two major outcomes: the development of end-stage renal disease and mortality rates in the first 5 years after LN diagnosis. Methods: An observational retrospective study of patients with LN, followed up from 1975 at University College Hospital. Patients were divided into four groups, depending on the decade of LN diagnosis: 1975–1985 (D1), 1986–1995 (D2), 1996–2005 (D3) and 2006–2015 (D4). Comparison between groups was performed with respect to demographic, clinical, serological and histological characteristics and outcome. Results: Two hundred and nineteen patients with LN were studied. There was a change in ethnic distribution, with a decreasing proportion of Caucasians (58.6% in D1 to 31.3% in D4, P = 0.018) and increase in African-ancestry (17.2% in D1 to 39.6% in D4, P = 0.040). Serological and histological patterns changed throughout time, with a reduction in class IV nephritis (51.7% in D1 to 27.1% in D4, P = 0.035), and increase in class II nephritis (10% in D2 to 18.8% in D4, P = 0.01) and anti-extractable nuclear antigen antibody positivity (17.2% in D1 to 83.3% in D4, P = 0.0001). The 5-year mortality rates decreased from D1 (24.1%) to D2 (4%), stabilizing for the next 30 years. The 5-year progression to end-stage renal disease remained stable over the decades. Conclusion: Despite the changes in treatment of LN in the past 20 years, we have reached a plateau in 5-year mortality and progression to end-stage renal disease rates, suggesting that new therapeutic and management approaches, and strategies to enhance adherence, are needed to improve outcomes further in LN patients.